2021
DOI: 10.1111/1440-1681.13524
|View full text |Cite
|
Sign up to set email alerts
|

Potential of crocodile blood as a medication and dietary supplement: A systemic review

Abstract: Crocodile blood has long been used as a traditional medicine in many Asian countries to treat diseases such as asthma, allergies, and many others. Yet, only recently has the safety and effectiveness of using crocodile blood as a medicine been examined using modern scientific methods; with both conserved and novel active components identified from crocodile blood. Further in vitro and in vivo investigations found that crocodile blood can have a wide range of beneficial effects, including antimicrobial, antivira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 102 publications
(226 reference statements)
0
5
0
Order By: Relevance
“…Heavy metals, radiation, and pathogenic microorganisms are no match for a crocodile's resistance to these threats to its health. Earlier studies have shown that the lysates of several organs from the crocodile's body (heart, lungs, liver, brain intestines, bile, and gallbladder) have antibacterial anti-tumor effects [1], with antibacterial and woundhealing qualities features of crocodile blood [2]. Crocodile oil (CO) was shown to be effective in the treatment of asthma, emphysema, flu, persistent cough, phlegm-producing mucus, skin ulcers, burns, cancer, and wounds [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals, radiation, and pathogenic microorganisms are no match for a crocodile's resistance to these threats to its health. Earlier studies have shown that the lysates of several organs from the crocodile's body (heart, lungs, liver, brain intestines, bile, and gallbladder) have antibacterial anti-tumor effects [1], with antibacterial and woundhealing qualities features of crocodile blood [2]. Crocodile oil (CO) was shown to be effective in the treatment of asthma, emphysema, flu, persistent cough, phlegm-producing mucus, skin ulcers, burns, cancer, and wounds [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The discrepancy in findings between the two studies may be attributed to differences in participants' initial iron status. In addition, the study showed a single-time oral treatment of crocodile blood supplement that upregulated the antioxidative enzymes catalase and superoxide dismutase (Chook et al, 2021) may lead to an adaptive response resulting in increased resistance to oxidative stress, which is related to the relationship between VO2 and TNF-α inflammation in the exercising muscles (Rosado-Perez & Mendoza-Nunez, 2018). Another possible explanation for the lack of supplementation effect on lactate in the time trial is the large training effect observed in the study, which may have obscured any supplementation effect.…”
Section: Discussionmentioning
confidence: 99%
“…Blood from crocodilians has notably lower concentrations of copper, iron, and zinc compared with human and pig blood. Despite the substantial difference in iron content between fresh crocodilian and pig blood, the iron content of freeze-dried crocodile blood (164 mg/100 g) has been reported to be similar to that of freeze-dried pig (149.01 ± 3.81 mg/100 g) and chicken (181.66 ± 1.01 mg/100 g) blood (Chook et al, 2021). No studies have evaluated changes in hematological response and aerobic capacity with freeze-dried crocodile blood supplementation combined with hypoxic training.…”
Section: Introductionmentioning
confidence: 94%
“…FD is just one part of this diversity. Crocodylian blood has been found to contain antimicrobial peptides which may have future medical uses through anti‐tumour and anti‐bacterial ability (Chook et al, 2021). These potential uses of crocodylian peptides provide a clear example of an unanticipated value, and conserving crocodylians thus enhances our chances of having such options in the future (Molina‐Venegas et al, 2021).…”
Section: Discussionmentioning
confidence: 99%